Educational Leadership for E-Learning in the Healthcare Workplace - Fahlman, Dorothy (Willy) (International Review of Research in Open and Distributed Learning, 2012)
Effective educational leadership can make a difference in the resolution of complex issues that impact today’s demand-driven educational marketplace. The ongoing professional and skill development needs of human health resources may be best managed through distributed strategic leadership blended with servant leadership. Together these two approaches may offer the critical bridge for effective educational leadership for e-learning within the healthcare workplace.